1989
DOI: 10.1111/j.1530-0277.1989.tb00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Proliferative Response of Con A‐blast Cells to Interleukin 2 in Adult Rats Exposed to Ethanol in Utero

Abstract: The fetal alcohol syndrome is associated with altered immunity. We attempted to delineate the mechanism of the decline in cell-mediated immunity observed by others by using rats which were exposed to alcohol in utero and tested for immune integrity 3 months after birth. We found that concanavalin A-stimulated T-lymphoblast (Con A T-blast) cells that were obtained from ethanol-exposed rats had significantly diminished proliferative responses to both crude and recombinant interleukin 2 compared to those obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Consistent with this latter possibility, we found reduced lymph node lymphocyte proliferative responses to Con A in PAE animals overall on day 7, and in PAE animals in the Adj/NA condition on day 16. These data replicate and extend previous results from our laboratory (Weinberg and Jerrells, 1991) and others (Ewald and Frost, 1987; Norman et al, 1989) demonstrating reduced splenic and thymic lymphocyte proliferative responses to mitogens, as well as reduced thymic and splenic T-cell responses to a secondary stimulation by IL-2. Blunted proliferation at induction of arthritis could reduce cytokine production and recruitment of cells to the joints, thus delaying arthritis onset.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with this latter possibility, we found reduced lymph node lymphocyte proliferative responses to Con A in PAE animals overall on day 7, and in PAE animals in the Adj/NA condition on day 16. These data replicate and extend previous results from our laboratory (Weinberg and Jerrells, 1991) and others (Ewald and Frost, 1987; Norman et al, 1989) demonstrating reduced splenic and thymic lymphocyte proliferative responses to mitogens, as well as reduced thymic and splenic T-cell responses to a secondary stimulation by IL-2. Blunted proliferation at induction of arthritis could reduce cytokine production and recruitment of cells to the joints, thus delaying arthritis onset.…”
Section: Discussionsupporting
confidence: 91%
“…Delayed thymic ontogeny, decreased total numbers of splenic and thymic T cells, decreased thymus weight, size, and cell counts, and suppressed B cell development have all been observed in fetuses and newborns exposed to alcohol in utero (Ewald and Walden, 1988; Ewald and Huang, 1990; Clausing et al, 1996; Moscatello et al, 1999). These changes may persist into adolescence and adulthood, and additional immune deficits, including altered responses to the intestinal parasite, Trichinella spiralis and deficits in mitogen-induced lymphocyte and lymphoblast cell proliferation to mitogens, may be revealed as the animal matures (Ewald and Frost, 1987; Ewald, 1989; Norman et al, 1989; Redei et al, 1989; Gottesfeld et al, 1990; Weinberg and Jerrells, 1991; Steven et al, 1992; Redei et al, 1993; Giberson and Blakley, 1994; Clausing et al, 1996; Seelig et al, 1996; Jerrells and Weinberg, 1998; Taylor et al, 1999). Moreover, exposure to stressors, including cold stress and chronic intermittent stress, may exacerbate immune deficits in PAE compared to control animals (Giberson and Weinberg, 1995; Giberson et al, 1997).…”
mentioning
confidence: 99%
“…2, B and C). On days 14 and 21, E-PL offspring continued to weigh less than pairfed (PF-PL) and control offspring ( p's < 0.00 1) (Fig. 2B).…”
Section: Maternal and Offspring Weights During Lactationmentioning
confidence: 90%
“…Recent studies have demonstrated that prenatal ethanol exposure also causes a variety of immunological abnormalities. [13][14][15][16][17][18][19][20][21][22][23] To investigate the effects of ethanol exposure during immune system maturation, we exposed neonatal mice to ethanol via the breast milk. Because the early postnatal period is characterized by development and maturation of immunocompetence,27 we hypothesized that ethanol exposure restricted to this stage of development may result in an alteration in the surface antigen phenotype of splenic lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies have suggested that lymphocyte numbers and proliferation in responses to mitogen stimulation are reduced also in adult rats exposed to EtOH in utero (4, 12, 13, 19). Further, young adult mice exposed to EtOH in utero also have decreased contact hypersensitivity and graft versus host responses (14), suggesting the effects of ethanol exposure on immunity can last into adulthood.…”
Section: Introductionmentioning
confidence: 99%